Behavior Of Consuming Betel Nut On The Incidence Anemia In Pregnant Women At Posyandu Wasur Kampung, Working Area Of Rimba Jaya Health Center Merauke District - Merauke Regency - Siti Sawiah; Erma Retnaningtyas; Retno Palupi Yonni Siwi; Anggrawati Wulandari (Journal of Health Science Community, 2024)
The incidence of anemia suffered by pregnant women at the Wasur Kampung Posyandu was caused by the majority of respondents consuming betel nut which has become a culture in the WasurKamping community. This study aims to determine the behavior of consuming betel nut on the incidence of anemia in pregnant women. This study uses a secondary data research design of anemia with a cross sectional approach. With the Total Sampling technique , a sample of 25 respondents was obtained, the independent variable of betel nut consumption using a questionnaire and the dependent variable of anemia incidence by looking at the records in the Register of Pregnant Women Cohort Wasur Kampung was used by the Spear-Mann statistical test to determine the relationship between the two variables. The results of the study from 25 respondents were obtained that most of the respondents consumed betel nut as many as 20 respondents (80%), of the 20 respondents who consumed betel nut areca nut all consumed betel nut ≥ 2 times a day and ≥ 2 pieces a day (100%). And it was found that most of the 20 respondents who consumed betel nut had moderate anemia as many as 17 people (85%). The analysis using the Non-Parametric Spear-Mann test obtained a correlation coefficient of 0.403*. This means that the level of strength of the relationship (correlation) between the free variable and the bound variable is 0.403 or strong. Based on the output, it is known that the significance value or Sig. (2-tailed) is 0.046, because the value of Sig. (2-tailed) 0.046 > is smaller than 0.05 or 0.01, it means that there is a significant relationship between areca nut consumption and the incidence of anemia.